2017
DOI: 10.1515/aep-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical stability of tap water in terms of required level of technological safety

Abstract: Abstract:The main goal of this work is to show the new approach to determining safety technological levels (SLs) in terms of water quality and its chemical stability, as well as issues of water corrosion properties in water distribution systems (WDSs), due to the fact that water supply pipes are prone to corrosion. In the paper the methodology of determining the risk associated with threat to technical infrastructure was considered. The concept was studied on the basis of real operational data from the water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In earlier research, Pietrucha et al confirmed that tap water supplying the experimental system is chemically unstable water with a tendency to solve solids with the possibility of occurrence of slight corrosion [30].…”
Section: Discussionmentioning
confidence: 91%
“…In earlier research, Pietrucha et al confirmed that tap water supplying the experimental system is chemically unstable water with a tendency to solve solids with the possibility of occurrence of slight corrosion [30].…”
Section: Discussionmentioning
confidence: 91%
“…goes to four chambers with carbon filters, and from there to clean water reservoirs specific to WTPI and WTPII [36]. The treated water meets the quality requirements set for water intended for human consumption [37,38], while the quantity produced each day is around 37,000 m 3 -enough to meet the customers' needs in full.…”
Section: The Concept Of the Fault Tree Methodsmentioning
confidence: 99%
“…The intermediate ozone chambers are completely separate for WTP I and WTP II . Water after ozonization goes to four chambers with carbon filters, and from there to clean water reservoirs specific to WTP I and WTP II [36].…”
Section: Characteristics Of the Research Objectmentioning
confidence: 99%
See 1 more Smart Citation
“…Biologically stable water should not support any adverse changes in bacteriological parameters [14,15]. In turn, lack of chemical water stability, as determined by some physico-chemical water indices, may lead to the electrochemical corrosion of metallic surfaces, or as was mentioned earlier, to calcium compounds being deposited and leached from pipes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%